Evaluating heuristic for EG portal design model - Mahmud, Murni; Che Hussin, Ab Razak; Othman, Noor Khairunnisa; Mohamed Dahlan, Halina (2010)
The effective use of an E-Government (EG) Portal depends on the ability of people to utilize electronic services. One of the main challenges in developing the EG Portal is selecting usability design guidelines that addressed the overall EG functions. Most government agencies tend to design their portal based on existing guidelines that are not directly related to the EG context. In this study, the basic functions and characteristics of the EG Portal were analyzed. The concept of usability, the design guidelines, and the heuristic were reviewed. A set of questionnaires was distributed to users to access its accuracy of the proposed heuristic for design model of EG Portal. The result indicates that the heuristic in the design model could reduce the usability problems in the portal.